Clinical observation of the efficacy of PD‐1/PD‐L1 inhibitors in the treatment of patients with advanced solid tumors - Miao Wang (Wiley, 2021)
Abstract Introduction Programmed death 1 (PD‐1)/programmed death‐ligand 1 (PD‐L1) inhibitors are proved to be promising and are applied for the treatment of a variety of solid tumors. This retrospective study evaluated the efficacy of PD‐1/PD‐L1 inhibitors in patients with advanced solid tumors and explore the effect of clinical characteristics on it. Materials and Methods From October 2017 to April 2020, a total of 90 patients from Capital Medical University Affiliated Beijing Friendship Hospital were enrolled. Results At a median follow‐up of 10.55 months, objective response was observed in 23 patients and the objective response rate was 25.6%. The median progression‐free survival (PFS) was 5.5 months (95% confidence interval [CI], 3.69–7.37). The 6m‐PFS was 45.8% and 12m‐PFS was 25.1%. The median overall survival (OS) was 16.9 months (95% CI, not reached [NR]‐NR). The 12m‐OS was 58.1% and 18m‐OS was 48.1%. Conclusion The efficacy of PD‐1/PD‐L1 inhibitors in the treatment of advanced solid tumors was comparable to previous studies. ECOG performance status, smoking status, liver metastasis, neutrophil‐to‐lymphocyte ratio were independently correlated with PFS while liver metastasis and lactate dehydrogenase level were independently correlated with OS.